LITERASI REFLEKTIF BERBASIS NARASI LOKAL DI SMPN 1 LOA JANAN KABUPATEN KUTAI KARTANEGARA: Reflective Literacy Based on Local Narratives at SMPN 1 Loa Janan, Kutai Kartanegara Regency - Arifin, M. Bahri; Yohana, Saferi; Prafitri, Wilma (Jurnal Ruhui Rahayu: Jurnal Pengabdian Masyarakat Ilmu Humaniora, 2025)
Abstract: This community engagement initiative sought to enhance students' reflective literacy by utilizing local cultural narratives at SMPN 1 Loa Janan, Kutai Kartanegara Regency. The program addressed two primary concerns: the deficiency in students' reflective literacy and the restricted incorporation of local culture in literacy activities. The methodology encompassed five interconnected phases: program socialization and participatory mapping, literacy instruction, creative writing workshops, mentorship, and assessment. Data were gathered by observation, pre-test and post-test assessments, and documentation of students' written assignments. The findings demonstrated a marked enhancement in students' comprehension of narrative structure and their capacity to relate local stories to modern circumstances. Creative writing exercises, such as "unusual stories," fostered inventiveness, confidence, and expressive ability among participants. The curriculum fostered a participatory literacy environment within the school, incorporating cultural identification and reflective thought. This effort proved that local narratives can effectively underpin the development of sustained and contextually relevant literacy initiatives in educational institutions. Keywords: junior high school; loa janan; local culture; narrative writing; reflective literacy   Abstrak: Program pengabdian kepada masyarakat ini bertujuan untuk memperkuat literasi reflektif siswa melalui narasi yang berlandaskan budaya lokal di SMPN 1 Loa Janan, Kabupaten Kutai Kartanegara. Aktivitas ini merespons dua isu utama, yaitu rendahnya literasi reflektif siswa dan kurangnya pemanfaatan budaya lokal dalam inisiatif literasi sekolah. Metode pelaksanaan terdiri dari lima tahap: sosialisasi dan pemetaan partisipatif, pelatihan literasi, lokakarya penulisan kreatif, pendampingan, dan evaluasi. Data dikumpulkan melalui observasi, pre-test, post-test, dan dokumentasi karya tulis siswa. Hasil kegiatan menunjukkan peningkatan signifikan dalam pemahaman struktur naratif dan kemampuan mengaitkan cerita lokal dengan konteks kekinian. Aktivitas menulis kreatif seperti "cerita kreatif" berhasil mengembangkan imajinasi, kepercayaan diri, dan kemampuan ekspresif siswa. Program ini berkontribusi pada pengembangan ekosistem literasi partisipatif di sekolah melalui integrasi identitas budaya dan refleksi diri. Aktivitas ini menunjukkan bahwa narasi lokal dapat berfungsi sebagai fondasi yang efektif dalam mengembangkan gerakan literasi yang kontekstual dan berkelanjutan di institusi pendidikan. Kata kunci: budaya lokal; literasi reflektif; Loa Janan; penulisan naratif; SMPN 1